Titanium Incorporation into Zr‐Porphyrinic Metal–Organic Frameworks with Enhanced Antibacterial Activity against Multidrug‐Resistant Pathogens - Chen, Mian; Long, Zhou; Dong, Ruihua; Wang, Le; Zhang, Jiangjiang; Li, Sixiang; Zhao, Xiaohui; Hou, Xiandeng; Shao, Huawu; Jiang, Xingyu (Small (Weinheim an der Bergstrasse, Germany), 2020)
This study uses metal–organic frameworks (MOFs) alone without any added antibacterial ingredients as the nonantibiotic agent for photodynamic therapy (PDT) of chronic wounds infected by multidrug‐resistant (MDR) bacteria. Nanoparticles (NPs) of MOFs (PCN‐224) are incorporated with titanium through a facile cation exchange strategy. The obtained bimetallic PCN‐224(Zr/Ti) shows greatly enhanced photocatalytic performance for the generation of reactive oxygen species under visible light, which is responsible for the effective antibacterial activities. The PCN‐224(Zr/Ti) NPs are loaded onto lactic‐co‐glycolic acid nanofibers to prepare a wound dressing, which shows high biocompatibility and minimal cytotoxicity. The wound dressing is efficient for PDT‐based in vivo healing of the chronic wound infected by MDR bacteria. Most importantly, this work does not involve any additional antibacterial agents, which is facile, low cost, and in particular, greatly explores the potential of MOFs as a powerful nonantibiotic agent in PDT. This study uses metal–organic frameworks alone without any added antibacterial ingredients as the nonantibiotic agent for photodynamic therapy of chronic wounds infected by multidrug‐resistant bacteria. The Ti incorporation could greatly boost the generation of reactive oxygen species for effective elimination of multidrug‐resistant bacteria, and the validated biocompatibility of PCN‐224(Zr/Ti) would ensure the biosafety for photodynamic therapy.